Association between multimorbidity with cognitive dysfunction in a Peruvian population - Carrasco-Zavala, J. (2023)
Background:Previous studies have shown that multimorbidity is a risk factor for cognitive dysfunction (CD).Type 2 diabetes mellitus (T2DM) and hypertension (HT) are very common risk factors.The association between multimorbidity due to both diseases and CD has been understudied in low and middle-income countries, in which the strength of the association might be stronger. Aim: To evaluate the association between multimorbidity due to T2DM and HT with CD among adults ≥50 years in Tumbes. Materials and methods: A secondary analysis of a population-based cross-sectional study was conducted. The exposure variable was the presence of both T2DM and HT, split into categories: without HT or T2DM, only T2DM, only HT, and with T2DM and HT; whereas CD was the outcome variable, defined as a score ≤26 in the Leganes Cognitive Test. Crude and adjusted generalized linear models were used to estimate the association of interest, and prevalence ratio (PR) and 95% confidence interval (95%CI) were reported. Results: 688 participants were analyzed. The prevalence of CD was 39.1%. There was a 56.1% of participants without TDM2 nor HT, 8.3% with T2DM, 28.9% with HT and 6.7% with both diseases. A significant association was found between multimorbidity and CD (PR = 1.43, 95%CI 1.04–1.97). Multimorbidity had a statistically significant association with CD in the group of participants with ≥7 years of education (PR = 2.56,95%CI 1.55–4.21), but no in the group with <7 years. Conclusions: There is association between the morbidity of T2DM and HT, and CD among adults ≥50 years of age in Tumbes. Education was an effect modifier of the association between HT and T2DM on the presence of CD.